UNPACKING RACIOLINGUISTIC IDEOLOGY IN YOUNG ADULT FICTION: A TEXTUAL ANALYSIS OF NOVEL “FRONT DESK” BY KELLY YANG - Nirwana; Aceng Ruhendi Saifullah; Mutakhirani Mustafa; Zulfiana Amaliana MZ (UIN Alauddin Makassar, 2023)
Abstract This study examines the representation of raciolinguistic ideologies in Young Adult Fiction, with a particular focus on Kelly Yang's novel